Differentiation of microfluidic‐encapsulated trabecular meshwork mesenchymal stem cells into insulin producing cells and their impact on diabetic rats. Issue 5 (14th October 2018) - Barati, Ghasem; Nadri, Samad; Hajian, Ramin; Rahmani, Ali; Mostafavi, Hossein; Mortazavi, Yousef; Taromchi, Amir Hossein
Abstract: Tissue and stem cell encapsulation andtransplantation were considered as promising tools in the treatment of patients with diabetes mellitus. The aim of this study was to evaluate the effect of microfluidic encapsulation on the differentiation of trabecular meshwork mesenchymal stem cells (TM‐MSC), into insulin‐producing cells (IPCs) both in vitro and in vivo. The presence of differentiated cells in microfibers (three dimensional [3D]) and tissue culture plates (TCPS; two dimensional [2D]) culture was evaluated by detecting mRNA and protein expression of pancreatic islet‐specific markers as well as measuring insulin release of cells in response to glucose challenges. Finally, semi‐differentiated cells in microfibers (3D) and 2D cultures were used to control the glucose level in diabetic rats. The results of this study showed that MSCs differentiated in alginate microfibers (fabricated by microfluidic device) express more Pdx‐1 mRNA (1.938‐fold, p ‐value: 0.0425) and Insulin mRNA (2.841‐fold, p ‐value: 0.0001) compared with those cultured on TCPS. Furthermore, cell encapsulation in microfluidic derived microfibers decreased the level of blood glucose in diabetic rats. The approach used in this study showed the possibility of alginate microfibers as a matrix for differentiation of TM‐MSCs (as a new source) into IPCs. In addition, it could minimize different steps in stem cell differentiation, handling, and encapsulation, which lead to loss of an unlimited number of cells.